Three-Year Assault Cases Performed on the Emergency Trauma Center - Melih Yucel SANLIER; Behcet Al; Volkan CELEBI; Gorkem Alper SOLAKOGLU; Eltaf TORUN; Kurtulus ACIKSARI; Bilgehan Ahmet CUMHUR; Nafiye SANLIER (Medeniyet Medical Journal)
Objective: This study aims to compare the results of cases with a history of assault presented to our emergency department over a period of three years with literature data and to share our experiences with colleagues. Methods: Demographic characteristics, trauma findings, clinical conditions, surgical interventions, mortality, and outcomes of patients with a history of assault to the emergency department between 2020 and 2022 were retrospectively examined. The results were analyzed using the Number Cruncher Statistical System 2007 Statistical Software package program (Utah, USA). Results: A total of 2900 patients, including 1850 males (63.79%) and 1050 females (36.21%), with an average age of 35.53+-12.46 years, were included in the study. Most admissions (31.28%) occurred during the summer months and outside working hours. Males inflicted all injuries. The most common injuries occurred in the head-neck region (63.31%) and upper extremities (47.97%) in both sexes. Facial injuries were significantly more common in males (p=<0.05), whereas spinal and pelvic injuries were common in females (p<0.05). Tenderness, edema, hematoma, abrasion, ecchymosis, and soft tissue laceration were the most frequently observed findings. Female patients were more likely to be discharged home (p=0.0001), whereas male patients had a higher hospitalization rate (p=0.0001). Life-threatening ailments were discovered in 23 patients (0.79%). Surgical intervention was performed in 50 patients (1.72%). No patient experienced fatal outcomes. Conclusions: All assaults were committed by males. Males are more frequently and severely assaulted than females. The victims were mainly from young people, and assaults predominantly occurred during the summer months and outside working hours. Head-neck and extremity injuries were the most common. There were no fatal outcomes. Nine of the 10 patients were discharged to home from the emergency department.